Notes on quality management in building/Bemerkungen zum qualitätsmanagement im bauwesen - Peldschus, Friedel (Journal of Civil Engineering and Management, 1997)
At present we can see how the quality of building production presents many facts for dissatisfaction. The amount of losses is extremely large and the national economy cannot tolerate it. In the EU attempts were made to solve quality problems by organizational means. Consequently, in the 1980s appeared and in 1994 were altered the codes ISO 9000 which are to be used up to 2004. On the other hand, a different tendency may be observed. So-called “lean production” in Japan industry showed that good quality can also be achieved by low prices. It should be mentioned that the above-mentioned experience and knowledge are first of all applied to industry. Hence they cannot be adopted directly in building construction. A control through self-control is an essential part of quality management. Self-control becomes an effective means when tasks and steps are formulated in written form. This process is divided into 10 steps. The application of this system encounters many difficulties. The principal difference between building construction and industry is that in building construction separate, not serial, objects prevail. Every client expresses individual demands for building structures. A successful quality management must embrace all phases. Besides, the common interconnection points of contracting and interested parts are very important, too. Quality management should clearly define the responsibilities at an enterprise. A correctly treated and applied quality management should optimise the inner processes and structures of an undertaking; the employees should be motivated and all the participant of building processes are to be effectively co-ordinated. Kokybės vadybos statyboje pastabos Santrauka. Šiuo metu galime pastebėti, kad statybos produkcijos kokybė teikia daug pagrindo nepasitenkinimui. Nuostolių mastas toks didelis, kad liaudies ūkis daugiau to negali toleruoti. Europos Sąjungoje buvo bandyta kokybės problemą spręsti organizacinėmis priemonėmis. Taip apie 80-uosius metus atsirado ir 1994 buvo perdirbtos normos ISO 9000, kurios turi galioti iki 2004 metų. Tačau pastebima ir kita tendencija. Ypač Japonijos pramonėje praktikuojamas “lean production” parodė, kad gerą kokybę taip pat galima pasiekti žmomis kainomis. Reikia pasakyti, kad minėtas patyrimas ir žnios visų pirma taikomos masšinų pramonėje. Jos negali būti tiesmukisškai perkeltos į statybą. Kontrolė per savikontrolę yra esminė kokybės vadybos dalis. Savikontrolė tampa efektyvijei uždaviniai ir žingsniai yra suformuluoti raštu. Šis procesas suskirstomas į dešimt žngsnių. Šios sistemos naudojimas statyboje sukelia sunkumų. Pagrindinis statybos skirtumas nuo pramonės yra tai, kad čia dominuoja atskiri, ne serijinės gamybos ir ne vienodi objektai. Kiekvienas užakovas turi individualių pretenzijų statiniams. Sėkminga kokybės vadyba privalo aprėpti visas fazes. Be to, labai svarbios yra sutarties ir suinteresuotų partnerių bendros sąlyčo vietos. Kokybės vadyba privalo aiškiai nustatyti atsakomybes įmonėje. Teisingai suprasta ir naudojama kokybės vadyba turi optimizuoti vidinius įmonės procesus ir struktūras, o bendradarbius motyvuoti bei visus statybos dalyvius efektyviai koordinuoti. Article in German. First Published Online: 26 Jul 2012